2012
DOI: 10.1007/s12149-012-0635-y
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of F-18 fluorodeoxyglucose positron emission tomography/computed tomography in patients with Langerhans cell histiocytosis

Abstract: Results of this study suggest that F-18 FDG PET/CT is useful for identification of active lesions, stratification of disease stages, monitoring of therapeutic response, and detection of reactivation in LCH patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…PET, integrated with computed tomography (CT) is an important and informative study that demonstrates metabolic tumor function with anatomical localization used for diagnosis, RT planning and treatment response. Due to the rarity of LCH, only a few authors have demonstrated the usefulness of FDG PET or PET/CT for identification of metabolically active lesions or monitoring of therapeutic response in patients with LCH [5,10,11]. In our case, since the disease site was quite large and the tumor was infiltrating surrounding tissues, it was difficult to differentiate the tumor from soft tissues with conventional CT.…”
Section: Discussionmentioning
confidence: 90%
“…PET, integrated with computed tomography (CT) is an important and informative study that demonstrates metabolic tumor function with anatomical localization used for diagnosis, RT planning and treatment response. Due to the rarity of LCH, only a few authors have demonstrated the usefulness of FDG PET or PET/CT for identification of metabolically active lesions or monitoring of therapeutic response in patients with LCH [5,10,11]. In our case, since the disease site was quite large and the tumor was infiltrating surrounding tissues, it was difficult to differentiate the tumor from soft tissues with conventional CT.…”
Section: Discussionmentioning
confidence: 90%
“…Histologically, histiocytosis is characterized by clonal proliferation of histiocytes, which in turn triggers an intense immune response by recruiting cooperating inflammatory cells . Glucose metabolism correlates with cellular proliferation in many tumours and, by exploiting this characteristic, 18 F‐FDG PET/CT has been previously used for detecting and monitoring the response of other histiocytoses, such as LCH . Until now, the diagnosis of XD has been based on pathological and clinical grounds.…”
Section: Discussionmentioning
confidence: 99%
“…The other sites of involvement include lung, ear, eye, liver, spleen, lymph node, central nervous system, etc. 2 Because the lesions are characterized by proliferation of histiocytes, they commonly show increased 18 F-FDG uptake. 3 Thus, 18 F-FDG PET/CT helps in detecting the extent of involvement (staging) of the disease.…”
Section: Figurementioning
confidence: 99%
“…It helps in choosing the treatment options and is also useful in prognostication of the disease. 2 Amyloidosis associated with LCH is extremely rare. 4 Extracellular deposition of insoluble polymeric protein fibrils in tissues and organs is characteristic of amyloidosis.…”
Section: Figurementioning
confidence: 99%